THE EFFECT OF USING BIGBOX APPLICATION ON STUDENTS’ READING COMPREHENSION OF THE TENTH GRADE - Nita Pratama; Meida Rabia Sihite; Sofia Idawati Lubis (English Education Study Program FKIP Universitas Alwashliyah Medan, 2022)
The objective of this research was to investigate if BIGBOX application significantly affected students’ reading comprehension at SMK Swasta Yaspenmas Sei Lepan. The research design used was experimental research. The population of this research was the whole students of the tenth grade which were distributed into two parallel classes, namely X-1 and X-2. The sampling technique used was cluster random sampling. It was obtained that X1 was selected as the experimental group and X-2 was selected as the control group. Each class consisted of 30 students, thus the total sample was 60 students. The experimental group was taught reading comprehension using BIGBOX application while the control group was taught in traditional way. The research instrument used was a reading test with multiple choices. The data obtained were analyzed by using statistical analysis of t-test formula. It was found out that the t-observed value was 2.184 and the t-table value was 2.002 at level of significance P= 0.05 and df=58. Based on the value obtained, the hypothesis testing proved that the alternative hypothesis was accepted and null hypothesis was rejected. The research concluded that BIGBOX application effected students’ reading comprehension.